Current understanding of the roles of gut–brain axis in the cognitive deficits caused by perinatal stress exposure - Rubinstein Guichón, Mara Roxana (2023)
Fil: Rubinstein Guichón, Mara Roxana. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Psiconeuroendocrinoinmunología; Argentina